Efficient Experimental Design of a Long-Range Gapped Surface Plasmon Polariton Waveguide for Plasmonic Modulation Applications - Dong Hun Lee; Myung-Hyun Lee (IEEE Photonics Journal, 2019)
We propose straight and tapered insulator–metal–insulator-type surface plasmon polariton (SPP) waveguides with a gap (G-SPPWs). The optical characteristics of the G-SPPWs are experimentally evaluated at a wavelength of 1.55 μm due to optical communication gateway. The parameters of the 20-nm-thick G-SPPWs were chosen based on our previous simulation results. The excited input SPPs propagate, jump over the gaps with low coupling losses, and propagate again, despite a 9-μm-long gap in the G-SPPWs. The coupling losses of the gap were experimentally determined to be less than 0.7 dB with various gap lengths up to 9 μm. The insertion losses of the straight G-SPPW with 8 μm × 2 μm (gap length × SPPW width) and the tapered G-SPPW with 8 μm × 2 μm (gap length × SPPW width) and a 6 μm × 3 μm (taper width × taper length) were determined to be ∼1.03 and ∼0.74 dB, respectively. The tapered structure increases the tunneling efficiency in the gap of the G-SPPW by reducing the insertion loss. In the 2.5-Gbps optical signal transmission experiment, the proposed G-SPPW exhibited excellent eye opening and transferred the carrier wave as well as the data signal. This device has potential as a new plasmonic modulation element offering control of a guided SPP through interaction with an applied force in the gap.